Investigation of FinFET as a Temperature Nano-Sensor Based on Channel Semiconductor Type - Hashim, Yasir (IOP Publishing, 2017)
This paper represents the temperature effect on FinFET transistor and the possibility of using it as a temperature nano-sensor. The MuGFET simulation tool was used to investigate temperature characteristics of the FinFET. Current-voltage characteristics with different values of temperature were simulated. MOS diode connection suggested using the FinFET transistor as a temperature nano-sensor. The final results shows that the best FinFET used as a nanosensor is with GaAs because it has the greatest ∆I (=10.9%) referring to ∆I at 25o C, and the best FinFET stable with increasing working temperature is Si-FinFET because it has the lowest ∆I (=6%) referring to ∆I at 25 C.